2009
DOI: 10.5005/johcd-3-3-45
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Factors and Child's Dental Health

Abstract: Aim: This study was carried out to investigate the effect of mother' s age, education, occupation and income on the dental health behaviours and caries experience of her pre-school children in the District of Lahore, Pakistan.Methods: This questionnaire based cross-sectional study evaluated the dental health status and oral health behaviors of 600 children in relation to the mother' s age, education, family income and her domicile of residence. Chi square test was used to see the association between the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 12 publications
2
10
1
2
Order By: Relevance
“… 6 Most of the mothers have a very little knowledge regarding the oral hygiene practices which includes brushing, flossing, use of fluoride, etc. These findings correlate with the findings of Suresh et al 7 There was statistically difference between observed tooth brushing habits and reported by parents especially mothers which is similar to the findings of Mohebbi et al 8 Martins et al 9 In this study, mothers' preventive dental behavior was one of the factors which influenced the child's dental health and these findings are similar to the study conducted by Chen MS. 10 Younger mothers and mothers with high level of education have a better knowledge on use of toothbrush, toothpaste and these findings correlate with the previous studies done by Sufia et al 11 and Hosani et al 12 …”
Section: Discussionsupporting
confidence: 79%
“… 6 Most of the mothers have a very little knowledge regarding the oral hygiene practices which includes brushing, flossing, use of fluoride, etc. These findings correlate with the findings of Suresh et al 7 There was statistically difference between observed tooth brushing habits and reported by parents especially mothers which is similar to the findings of Mohebbi et al 8 Martins et al 9 In this study, mothers' preventive dental behavior was one of the factors which influenced the child's dental health and these findings are similar to the study conducted by Chen MS. 10 Younger mothers and mothers with high level of education have a better knowledge on use of toothbrush, toothpaste and these findings correlate with the previous studies done by Sufia et al 11 and Hosani et al 12 …”
Section: Discussionsupporting
confidence: 79%
“…The household income level was the sole factor in this association. Although previous studies have linked children’s dental health status and maternal education level, no statistically significant association was observed in this study [ 15 , 20 ]. The findings of this study therefore suggest that children who have experienced dental caries in low- and middle-income households are more likely to be associated with non-treatment than those from high-income households.…”
Section: Discussioncontrasting
confidence: 95%
“…The independent variables were related to parental SES (household income level and maternal educational level), which was obtained via the survey questionnaire. Previous studies reported a strong association between maternal factors and children’s dental health [ 20 , 21 ]. Therefore, maternal factors such as education level were used to measure parental SES.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The determinants of oral health behaviors are complex, as they comprise both daily toothbrushing routines and sugar snacking behaviors. 9 Toothbrushing routines and sugar snacking behaviors are practiced mainly within home, school, and community environments for primary school age children and are predominantly influenced by significant social relationships and behaviors of those around them, such as parents, 10 , 11 especially mothers, 12 , 13 siblings, 14 and peers, and other social, economic, and cultural factors. Toothbrushing usually takes place within a home environment that, in itself, may be complex due to variability in social and domestic family structure (eg, lone parent families) 15 and wider influences such as grandparents (who may have different attitudes and beliefs about toothbrushing than the parents).…”
Section: Background: Rationale For Oral Health Intervention In Primarmentioning
confidence: 99%